A Mathematical Model for the Relief Logistics in Humanitarian Supply Chain - Shahraki Moghaddam , Shabab; Sadeh , Ehsan; Amini Sabegh , Zeinolabedin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The coordination of relief supply chain actions following a crisis is undeniable and necessitates proper management and appropriate resource allocation to affected areas, especially due to the increasing occurrence of natural disasters such as floods, storms, and destructive earthquakes. The aim of this study is to design an integrated humanitarian supply chain system, considering the relationships among various components of the rescue and relief supply chain.Methodology: This research innovates over previous studies by proposing a five-level model comprising suppliers, warehouses, distributors, affected areas, and shelters within the supply chain; it also includes the location of relief warehouses and support facilities with an integrated dynamic model. Two categories of decisions are considered: the first involves selecting locations for regional warehouses from candidate sites and the quantity of pre-stocked inventory in them, and the second involves designing the distribution network and relief items, determining the flow of goods within it.Findings: The first objective of this issue is to minimize the construction costs of regional warehouses in Tehran under various scenarios, and the second objective is to minimize the costs of supply, maintenance of goods in regional warehouses; minimize the costs of sending and maintaining goods in the central warehouse; minimize the costs related to sending goods to demand points, and minimize the costs related to leftover goods in each region at the end of each period.Conclusion: The results show that the designed model optimizes the logistics costs of relief and rescue.